Peran Sensus Pertanian Dalam Mewujudkan Goals 2.4 SDGs - Zahwa Zalzabila Parhas (Madani: Jurnal Ilmiah Multidisiplin, 2023)
The agricultural census is an activity carried out by the government, in this case BPS as the organizer, which aims to provide agricultural structure data, especially for the smallest administrative units. The agricultural census is related to sustainable development goals (SDGs) point 2. This discussion aims to explain the role of data from the agricultural census as the key to an in-depth understanding of the agricultural sector and its contribution to global food security. Through a participatory approach, this article highlights the important role of farmers as primary data providers and advocates for agricultural sustainability. The emphasis on strengthening farmer participation and developing data-based policies is expected to make a significant contribution to achieving the SDGs, especially in the context of food security and sustainable agriculture.